Record of Ragnarok Vol. 1 - Umemura, Shin'ya; Fukui, Takumi (VIZ Media, LLC, 2022)
"Once every millennium, the gods assemble to decide if humanity is worthy of its continued existence or if it should be destroyed! When the verdict is destruction, the final battle between the gods and mortal heroes will decide the survival or extinction of the human race--a battle known as Ragnarok!" -- Cover.